The Impact of the COVID-19 Lockdown on Cancer Referrals in Primary Care in the UK: Two Years On - Olivia Whittle; Lucy Bushby; Rebecca Chambers; Jayden Gittens (International Journal of Medical Students)
BACKGROUND: Cancer is common, with most cancer patients presenting initially to a general care practitioner. The COVID-19 pandemic led to changes in the delivery of primary care, which could have affected cancer referrals. This observational study looked at cancer referrals made before, during and after the first UK COVID-19 lockdown in 2020, at a GP practice in the Wirral, England. METHODS: A search was conducted to find the cancer referrals made between 23rd March 2020 - 1st July 2020, during the first lockdown. Using the same methodology, cancer referral data was collected for the corresponding time periods in 2019 and 2021. The number of cancer referrals, and their positive diagnostic yields, were then compared.